Hubungan Partisipasi Siswa dalam Mengembangkan Koperasi Sekolah dan Hasil Belajar Mata Pelajaran Kewirausahaan dengan Minat Berwirausaha - Cici Kristinawati (Jurnal Salingka Nagari, 2022)
This research aims to determine. the relationship between student participation in developing school cooperatives and the learning outcomes of entrepreneurship subjects with the student’s entrepreneurial interests. This research uses quantitative approach with correlational type of research. Sampling technique used was random sampling. Research instruments used was questionnaires. Data analysis technique used pearson correlation test. The results showed that there was a strong relationship between student participation in developing school cooperatives and learning outcomes of entrepreneurship subjects with student’s entrepreneurial interests, student participation in developing school cooperatives has a very strong relationship with the student's entrepreneurial interests, and the learning outcomes of entrepreneurship subjects have a weak relationship with students' entrepreneurial interests. The results of this study can be used as a guideline to increase student’s entrepreneurial interests.